Improved Optical Probe for Measuring Phytoplankton Suspension Concentrations Based on Optical Fluoresensce and Absorption - Purnamaningsih, Retno Wigajatri; Prihantini, Nining Betawati (UI Scholars Hub, 2012)
This paper discusses the results of improved optical probe that works according to optical fluorescence and absorption phenomena for measuring the phytoplankton suspension concentrations. Measurements are made on the Scenedesmus sp. culture. The laboratory test has shown that range of concentration from 104 up to around 1 x 106 cells/mL; fluorescence intensity at λ = 685 nm; and logarithmic of transmission intensity at λ = 405 nm are proportional to the cell concentration linear with proportional constant γ = 4 × 10-5 and β = –2 × 10-7 mL/cell respectively.